The Influence of Intellectual Capital on the Profitability of Banking Companies - Agustin Sri Mutiara Gani; Rizan Machmud; Selvi Selvi (Universitas Negeri Gorontalo, 2020)
This research is motivated by a decrease in profitability in several companies over the last few years. The purpose of this study is to determine the effect of intellectual capital on the decline in profitability of banking companies over the past few years. This study has two types of variables consisting of dependent variables namely intellectual capital whose indicators are (VACA, VAHU, and STVA), while the independent variable is profitability whose indicators are represented by (ROE) in the 2013-2017 period. The results of this study indicate simultaneously VACA, VAHU, and STVA have an influence on company ROE. Partially VACA, and STVA have a significant influence on company ROE. Whereas VAHU has a negative influence on company ROE. 29.3% of all variables in this research model namely VACA, VAHU, and STVA have a contribution to affect profitability (ROE)